Effectiveness of a universal internet‐based prevention program for ecstasy and new psychoactive substances: a cluster randomized controlled trial. (13th April 2016) - Champion, Katrina E.; Newton, Nicola C.; Stapinski, Lexine A.; Teesson, Maree
Abstract: Aim: To evaluate the effectiveness of an online school‐based prevention program for ecstasy (MDMA) and new psychoactive substances (NPS). Design: Cluster randomized controlled trial with two groups (intervention and control). Setting: Eleven secondary schools in Australia. Participants: A total of 1126 students (mean age: 14.9 years). Intervention: The internet‐based Climate Schools : Ecstasy and Emerging Drugs module uses cartoon storylines to convey information about harmful drug use. It was delivered once weekly, during a 4‐week period, during health education classes. Control schools received health education as usual. Measurement: Primary outcomes were self‐reported intentions to use ecstasy and NPS at 12 months. Secondary outcomes were ecstasy and NPS knowledge and life‐time use of ecstasy and NPS. Surveys were administered at baseline, post‐intervention and 6 and 12 month post‐baseline. Findings: At 12 months, the proportion of students likely to use NPS was significantly greater in the control group (1.8%) than the intervention group [0.5%; odds ratio (OR) = 10.17, 95% confidence interval (CI) = 1.31–78.91]. However, students' intentions to use ecstasy did not differ significantly between groups (control = 2.1%, intervention = 1.6%; OR = 5.91, 95% CI = 1.01–34.73). There was a significant group difference in the change from baseline to post‐test for NPS knowledge (β =  − 0.42, 95% CI = −0.62 to −0.21, Cohen's d  = 0.77), with controls [mean = 2.78, standard deviation (SD = 1.48] scoring lower than intervention students (mean = 3.85, SD = 1.49). There was also evidence of a significant group difference in ecstasy knowledge at post‐test (control: mean = 9.57, SD = 3.31; intervention: mean = 11.57, SD = 3.61; β = −0.54, 95% CI = −0.97 to −0.12, P  = 0.01, d  = 0.73). Conclusions: The Climate Schools : Ecstasy and Emerging Drugs module, a universal online school‐based prevention program, appeared to reduce students' intentions to use new psychoactive substances and increased knowledge about ecstasy and new psychoactive substances in the short term.